2014
DOI: 10.1038/cddis.2013.499
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of hepatic apoptosis

Abstract: Apoptosis is a prominent feature of liver diseases. Causative factors such as alcohol, viruses, toxic bile acids, fatty acids, drugs, and immune response, can induce apoptotic cell death via membrane receptors and intracellular stress. Apoptotic signaling network, including membrane death receptor-mediated cascade, reactive oxygen species (ROS) generation, endoplasmic reticulum (ER) stress, lysosomal permeabilization, and mitochondrial dysfunction, is intermixed each other, but one mechanism may dominate at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
193
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(207 citation statements)
references
References 135 publications
(145 reference statements)
5
193
0
9
Order By: Relevance
“…25,26 Studies in knockout mice lacking NF-kB signalling components revealed an essential role of NF-kB in protecting the fetal liver from TNF-induced cell death. 21,22 We therefore hypothesized that the spontaneous apoptosis of NEMO-deficient hepatocytes that results in chronic hepatitis and HCC development in NEMO LPC-KO mice is driven by death receptor signalling.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Studies in knockout mice lacking NF-kB signalling components revealed an essential role of NF-kB in protecting the fetal liver from TNF-induced cell death. 21,22 We therefore hypothesized that the spontaneous apoptosis of NEMO-deficient hepatocytes that results in chronic hepatitis and HCC development in NEMO LPC-KO mice is driven by death receptor signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy subjects had no history or clinical evidence of previous or present illness. All patients in the ACLF group were managed according to the standard of care, including intensive care monitoring, high-calorie diet (35)(36)(37)(38)(39)(40) cal/kg/day), intravenous albumin, broad-spectrum antibiotics, pentoxifylline for alcoholic hepatitis, antivirals, which included tenofovir for hepatitis B virus (HBV) reactivation, terlipressin for hepatorenal syndrome, and lactulose bowel enemas. In the presence of acute kidney injury, the dose of tenofovir was modified according to creatinine clearance.…”
Section: Methodsmentioning
confidence: 99%
“…24 We found that at 24 hr after treatment, apoptotic cells decreased (2-fold) in the hucMSC-Ex group compared with the PBS and HFL-Ex groups (Figure 4A; n = 3; *p < 0.05, **p < 0.01). Hoechst 33342 staining revealed fewer apoptotic cells (half-moon nuclei) in the hucMSC-Ex group compared with the PBS and HFL-Ex groups ( Figure 4B; n = 3; *p < 0.05, **p < 0.01).…”
Section: Hucmsc-ex Inhibited Oxidative Stress-induced Apoptosismentioning
confidence: 84%
“…24 Thus, we measured changes in mitochondrial membrane potential in L02 cells treated with or without hucMSC-Ex using JC-1 staining. More cells were fluorescent green in the PBS and HFL-Ex groups, but more cells were fluorescent red in the hucMSC-Ex group (Figure 4Ci).…”
Section: Hucmsc-ex Inhibited Oxidative Stress-induced Apoptosismentioning
confidence: 99%